Keputusan Adopsi Benih Padi Bersertifikat melalui Program Desa Mandiri Benih oleh Petani di Kabupaten Boyolali - Iqbal Fadhlurrahman; Suminah Suminah; Arip Wijianto (Universitas Sebelas Maret, 2021)
Seeds Independent Village is a labor-intensive activity aiming at providing facilities to farmer groups to increase the capacity to produce seeds to fulfill the needs of seeds in their area. The objective of the study is to, examine the decision on adoption of certified rice seeds through the Seed Independent Village program, examine the factors that influence adoption decisions, examine the influence of factors that influence adoption decisions simultaneously and partially on adoption decisions. The research location was in Boyolali Regency. This research used quantitative methods with survey techniques. The population in this study was 1,200 farmers, members of the Berkah Gapoktan and Manunggal Makmur Gapoktan. Samples were taken using a proportional random sampling technique with a total of 120 farmers. Data analysis using logistic regression. The results showed farmers who implemented were aware of the existence of seed producers in their area, lower seed prices, and following the varieties needed, while farmers who did not implement were still using free seed assistance from the government and the varieties produced by Gapoktan were deemed incompatible with the needs of farmers; factors in the form of relative advantage, compatibility, complexity, trialability, observability were included in the high category, the social system and promotion efforts by agricultural instructors were in a low category, the types of communication channels included in the very low category; simultaneously, the factors that influenced adoption decisions had a significant effect. Partially the factors that had significant influence were complexity, trialability, and social system.